Educational leadership as a manifestation of ‘Adab’ in education: conception of Zarnuji - Paramboor, Jafar; Ibrahim, Mohd Burhan (Contemporary Research Center Australia, 2014)
‘The idea of one being over another is an anathema to modern man; but to the ancients, this was a sign of good breeding.’ (Yusuf, H., 2000). According to all kinds of religious concepts the educational leader is a unique model of inculcating the moral aspects of human life, to the one who is ‘led’ by him. Hence the reality of being ideally ruled becomes more meaningful. It is the function of an educational leader to move towards excellence in giving a guiding light to the coming generation by making them creative and dynamic. To accomplish the goal he will have to be a ‘fully committed guide’, not mere a ‘sharing instrument’. Admittedly the educational leader performance in our schools is going towards a downward motion (Yusuf, 2000). The present context has led us to rethink about the role of educational leaders in their fields and thus this paper will be focusing on the concept of Zarnuji, an eminent educational thinker, whose education theories have influenced many academicians throughout the world. The paper would briefly discuss the behavioral approach of an educational leader as a model which has been mentioned in his book,‘Ta’lim Al- MutaÑallim Tariq Al- TaÑallum’ (Instruction of the Student: the Methodology of Learning). It can be asserted that his viewpoint regarding the educational leadership policy is one of the best educational theories in Islamic tradition, which is yet to be applied by those who are accountable for a new Islamic thought of educational revival.